Exploration of Robotic Direct to Implant Breast Reconstruction - Alexis Parcells, MD; Scott Spiro, MD FACS (Plastic and Reconstructive Surgery, Global Open, 2020)
Breast reconstruction has undergone significant innovation over the past 50 years. Both the development of nipple sparing mastectomy and the use of acellular dermal matrices have facilitated the concept of direct to implant (DTI) reconstruction. The next step in this evolution is further limiting the length of incisions as well as placing access in a more remote location. A robot-assisted surgical approach for DTI reconstruction (R-DTI) with an acellular dermal matrix scaffold is feasible and addresses limitations with open approaches and ergonomics. The authors performed a cadaveric exploration to demonstrate proof of concept and feasibility for an R-DTI following a robot-assisted nipple sparing mastectomy. Tremor stabilization, direct visualization, endo-wristed robotic instrumentation, and exposure were noted as key benefits over existing open DTI reconstruction techniques. Additionally, the ability to have a more remote access to entry at the perimeter of the breast eliminated incisional tension which can jeopardize reconstructive results. Further exploration and procedure refinements are warranted.